The relationship between motivation and attitude towards English language achievement among students at UiTM Dungun Terengganu / Nor Zaitolakma Abdul Samad - Abdul Samad, Nor Zaitolakma (2014)
The aims of this study was to investigate students' motivation and attitude toward the learning of English language; to investigate students English language achievement and its component of listening, speaking, reading and writing and to determine the relationship between students' motivation and attitude toward their English language achievement. Comprising 329 randomly selected sampling for both Social Science and Science & Technology programme in UiTM Dungun, the study reveal that although students have a moderately high motivation and attitude towards English language learning, thus English language achievement attainment was low. The study also reveals that SES plays a significant role in English language learning and achievement. Students from high SES have a higher attainment in motivation, attitude and English language achievement as compared to their counterparts from lower SES. It is important for the government and policymakers to look into these matters on educational processes and provide equal education opportunities for those who are in need.